Sensory quality of upcycled legume water: Expectation vs. reality - Hippolite, Lauryn Rose; Feng, Ziqian; Zhang, Yanyu; Lee, Sung Je; Serventi, Luca (Frontiers in Food Science and Technology, 2023)
Aquafaba and Liluva are names used to define the processing water of food legumes. Large volumes of Liluva are generated by frozen pea manufacturers (blanching water) and tofu producers (tofu whey). Studies have shown the potential of Aquafaba and Liluva in food applications as texture improvers and sources of bioactive and prebiotics. Nonetheless, no information on consumer perception of these new food ingredients is available. Therefore, this study investigated consumer expectations of Steam Blanching Pea Water (SBPW) and Tofu Whey (TW), correlating it with their actual sensory quality and physicochemical functionality. Specifically, Liluva was used as a source of prebiotics and hydrocolloid in 3-D printed mashed potatoes to enhance their rheology and printability. A preliminary survey showed limited understanding of SBPW and TW as food ingredients, with only 43% and 38% of subjects willing to try TW and SBPW, respectively, with most subjects unsure on whether they wanted to or not (34% Tofu whey and 49% Liluva). Once the actual sensory test was commenced, TW-added mashed potato received favorable scores for all attributes (appearance, aroma, taste, texture). In contrast, SBPW-added mashed potato negatively impacted the color of mashed potatoes, as all 9 focus group subjects described the color as grey. Overall, TW enhanced the printability of mashed potatoes due to its emulsifying ability and possibly coagulants from tofu, and it was more appreciated sensory-wise, resulting in being the most preferred out of three samples (SBPW, TW and control). Therefore, emphasizing consumer education may be key when expanding these innovative food ingredients to other food areas.